(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2017)
In this paper the chemical and biological properties of the lake blue clay are explored. A blue clay bed layer was found under the sapropel layer in the lake Plusons (area 4.8 km2, Ludza countries, Latvia). It has been determined that the lake Plusons blue clay has a colloid composition, which contains Na, Mg, K, Ca, Fe, Cr, Mn, Co, Ni, Cu, Zn, Cd, Pb, Al, Ag, Ba. In samples Candida albicans, Pseudomona aeruginosa, Staphylococcus aureus and a total number of aerobic mezofile bacterium have been defined. In microbiological analyses the presence of Candida albicans, Pseudomona aeruginosa, Staphilacoccus aureus has not been stated. The number of mesophyll aerobic microorganisms is